2010
DOI: 10.1074/jbc.m110.119164
|View full text |Cite
|
Sign up to set email alerts
|

RecN Is a Cohesin-like Protein That Stimulates Intermolecular DNA Interactions in Vitro

Abstract: The bacterial RecN protein is involved in the recombinational repair of DNA double-stranded breaks, and recN mutants are sensitive to DNA-damaging agents. Little is known about the biochemical function of RecN. Protein sequence analysis suggests that RecN is related to the SMC (structural maintenance of chromosomes) family of proteins, predicting globular N-and C-terminal domains connected by an extensive coil-coiled domain. The N-and C-domains contain the nucleotide-binding sequences Walker A and Walker B, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 56 publications
5
65
0
Order By: Relevance
“…In vitro, purified RecN protein has been found to have a weak ATPase activity and DNA-bridging activity (Grove et al, 2009;Reyes et al, 2010). We found that cells lacking RecN protein did not compact or decompact the nucleoid after irradiation with a UV dose of 3 J m 22 (Fig.…”
Section: Recn Protein Is Required For Reorganization Of the Nucleoid mentioning
confidence: 76%
“…In vitro, purified RecN protein has been found to have a weak ATPase activity and DNA-bridging activity (Grove et al, 2009;Reyes et al, 2010). We found that cells lacking RecN protein did not compact or decompact the nucleoid after irradiation with a UV dose of 3 J m 22 (Fig.…”
Section: Recn Protein Is Required For Reorganization Of the Nucleoid mentioning
confidence: 76%
“…All four proteins, in particular RecJ, are required for normal cellular growth and recombinational repair (49). Recombinational repair is facilitated by RecN (DR1477), an SMC family member which tethers DNA molecules in a cohesin-like fashion and prevents the separation of DNA fragments (518). In B. subtilis, RecN is one of the first proteins recruited to DSBs (531).…”
Section: Recombinational Processes In D Radiodurans Dna Repairmentioning
confidence: 99%
“…In B. subtilis, RecN is one of the first proteins recruited to DSBs (531). In vitro, D. radiodurans RecN also stimulates the intermolecular ligation of linear DNA molecules in the presence of DNA ligase (518).…”
Section: Recombinational Processes In D Radiodurans Dna Repairmentioning
confidence: 99%
“…These results may reflect species-specific attributes of E. coli and B. subtilis HR pathways. The purified B. subtilis RecN (and also D. radiodurans RecN) binds to DNA and has DNA-stimulated ATPase activity in vitro (54,55). Unfortunately, it has been difficult to purify E. coli RecN because it is relatively insoluble and highly susceptible to degradation (data not shown).…”
Section: Recamentioning
confidence: 99%